2016
DOI: 10.1088/0029-5515/56/10/106025
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of ONIX simulation results with experimental data from the BATMAN testbed for the study of negative ion extraction

Abstract: The development of negative ion (NI) sources for the ITER neutral beam injector is strongly accompanied by modelling activities. The ONIX (Orsay Negative Ion eXtraction) code simulates the formation and extraction of negative hydrogen ions and co-extracted electrons produced in caesiated sources. The 3D geometry of the BATMAN extraction system and the source characteristics such as the extraction and bias potential, 3D magnetic field were integrated in the model. Calculations were performed using plasma parame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 30 publications
2
15
0
Order By: Relevance
“…For the simplest case of an electropositive hydrogen plasma with one positive ion specie (protons), potential sheath drops and sheath sizes of the presented analytical model were successfully benchmarked in 51 against two particle-in-cell codes ONIX 52,53 and BACON 21 and one analytical model 28 . Both ONIX and BACON enforce the Bohm criterion and the presheath voltage drop within 20 % when compared to fluid sheath results.…”
Section: Comparison Of Analytical and Particle-in-cell Resultsmentioning
confidence: 99%
“…For the simplest case of an electropositive hydrogen plasma with one positive ion specie (protons), potential sheath drops and sheath sizes of the presented analytical model were successfully benchmarked in 51 against two particle-in-cell codes ONIX 52,53 and BACON 21 and one analytical model 28 . Both ONIX and BACON enforce the Bohm criterion and the presheath voltage drop within 20 % when compared to fluid sheath results.…”
Section: Comparison Of Analytical and Particle-in-cell Resultsmentioning
confidence: 99%
“…For covering this aspect, 3D simulation codes resolving the plasma sheath are required. Among them is the ONIX code [46][47][48], which is a 3D particle-in-cell code using a self-consistent description of the plasma-wall interface in the presence of surface-emitted negative ions. Since 3D PIC codes resolving the plasma sheath are extraordinary computational demanding, only a small simulation domain can be used (one aperture, plasma a few mm upstream of the PG until the EG surface).…”
Section: Beam Extraction and Formationmentioning
confidence: 99%
“… Co-extracted electrons ONIX is the only code aiming to calculate and predict the co-extracted electron current. A dedicated benchmark shows good agreement for different extraction potentials and source conditioning [5]. As pointed out several times, the 3D topology of the magnetic field, in particular the deflection field in the extraction grid, plays a crucial role for such simulations.…”
Section:  Potential Wellmentioning
confidence: 64%
“…The Cs conditioning from experiments was modelled in ONIX by variation of the emission rate of negative ions from the plasma grid surface. It was found that the simulations were able to reproduce experimental results [5] by using the emission rate in the realistic range (50-550 A/m 2 ).…”
Section:  Variation With Cs Conditioningmentioning
confidence: 90%